Professionalism in Language Teaching? - Hardy, Jane E. (2013)
Language teaching is a profession that requires specialized skills. Teachers need a high level of proficiency in the language that they teach in addition to knowledge of second language acquisition and language teaching methodology. However, language teaching is frequently undervalued and misunderstood. This paper examines the (lack of) professionalism in language teaching from two different perspectives. First, the author considers the status of English language teaching around the world, which is adversely affected by the frequent practice of hiring unqualified native speakers. The second section of the paper addresses the current status of foreign language teaching in the United States. In spite of a critical need for foreign language skills in the U.S., language programs are being eliminated at universities around the country, and in some cases classroom instruction is being replaced with self-study software programs.